Ergonomics in Endoscopic Transsphenoidal Surgery: A Survey of the North American Skull Base Society - Mattogno, Pier Paolo; Marciano, Filippo; Catalino, Michael P.; Mattavelli, Davide; Cocca, Paola; Lopomo, Nicola Francesco; Nicolai, Piero; Laws, Edward R., Jr.; Witterick, Ian; Raza, Shaan M.; Devaiah, Anand K.; Lauretti, Liverana; Olivi, Alessandro; Fontanella, Marco M.; Gentili, Fred; Doglietto, Francesco (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Different surgical set-ups for endoscopic transsphenoidal surgery (ETS) have been described, but studies on their ergonomics are limited. The aim of this article is to describe present trends in the ergonomics of ETS.Design and Participants A 33-question, web-based survey was sent to North American Skull Base Society members in 2018 and 116 responded to it (16% of all members). Most respondents were from North America (76%), in academic practice (87%), and neurosurgeons (65%); they had more than 5 years of experience in ETS (73%), had received specific training (66%), and performed at least 5 procedures/mo (55%).Results Mean reported time for standard and complex procedures were 3.7 and 6.3 hours, respectively. The patient's body is usually positioned in a straight, supine position (84%); the head is in a neutral position (46%) or rotated to the side (38%). Most surgeons perform a binostril technique, work with a partner (95%), and operate standing (94%), holding suction (89%) and dissector (83%); sometimes the endoscope is held by the primary surgeon (22–24%). The second surgeon usually holds the endoscope (72%) and irrigation (42%). During tumor removal most surgeons stand on the same side (65–66%). Many respondents report strain at the dorsolumbar (50%) or cervical (26%) level. Almost one-third of surgeons incorporate a pause during surgery to stretch, and approximately half exercise to be fit for surgery; 16% had sought medical attention for ergonomic-related symptoms.Conclusion Most respondents value ergonomics in ETS. The variability in surgical set-ups and the relatively high report of complaints underline the need for further studies to optimize ergonomics in ETS.
Keywords: endoscopic transsphenoidal surgery; ergonomics; operating room set-up; patient position; surgeons; survey